Increasing fluency in L2 writing with singing - Alisaari, Jenni; Heikkola, Leena Maria (Studies in Second Language Learning and Teaching, 2016)
Fluency is an essential part of a language learner’s skills. Despite various studies on fluency, little is known about the effects of different pedagogical methods on the development of written fluency. In this paper, we examine how different pedagogical methods affect the development of second language learners’ written fluency. Participants in this study were 51 language learners enrolled in two intensive Finnish courses. The pedagogical methods investigated in the study were singing, listening to songs, and reciting lyrics of songs. Written stories based on cartoon strips were used as a pretest and a posttest. The fluency of written stories was analyzed based on the number of words used in the texts. Differences between the groups taught by different pedagogical methods were analyzed. The results seem to indicate that fluency increased the most in the singing groups compared to the other groups. There was also a statistically significant difference between the singing group and the group reciting lyrics, as well as between the group listening to songs and the group reciting lyrics.